A novel transcript isoform of STING that sequesters cGAMP and dominantly inhibits innate nucleic acid sensing. Issue 8 (14th March 2018) - Wang, Pei-Hui; Fung, Sin-Yee; Gao, Wei-Wei; Deng, Jian-Jun; Cheng, Yun; Chaudhary, Vidyanath; Yuen, Kit-San; Ho, Ting-Hin; Chan, Ching-Ping; Zhang, Yan; Kok, Kin-Hang; Yang, Wanling; et al.
Abstract: STING is a core adaptor in innate nucleic acid sensing in mammalian cells, on which different sensing pathways converge to induce type I interferon (IFN) production. Particularly, STING is activated by 2′3′-cGAMP, a cyclic dinucleotide containing mixed phosphodiester linkages and produced by cytoplasmic DNA sensor cGAS. Here, we reported on a novel transcript isoform of STING designated STING-β that dominantly inhibits innate nucleic acid sensing. STING-β without transmembrane domains was widely expressed at low levels in various human tissues and viral induction of STING-β correlated inversely with IFN-β production. The expression of STING-β declined in patients with lupus, in which type I IFNs are commonly overproduced. STING-β suppressed the induction of IFNs, IFN-stimulated genes and other cytokines by various immunostimulatory agents including cyclic dinucleotides, DNA, RNA and viruses, whereas depletion of STING-β showed the opposite effect. STING-β interacted with STING-α and antagonized its antiviral function. STING-β also interacted with TBK1 and prevented it from binding with STING-α, TRIF or other transducers. In addition, STING-β bound to 2′3′-cGAMP and impeded its binding with and activation of STING-α, leading to suppression of IFN-β production. Taken together, STING-β sequesters 2′3′-cGAMP second messenger and other transducer molecules to inhibit innate nucleic acid sensing dominantly.